Implementing the Concept of Poetry on Writing Greetings Card for EFL Junior High School Students - Vianti, Eri (EXCELLENCE: Journal of English and English Education, 2025)
Applying English verse into the English subject in schools is considered imperative to actuate students’ affectability on writing within the trust of conduct changing for understudies to gotten to be more mindful of writing. This investigate is pointed to discover out whether English verse can impact students’ composing aptitudes, so the analysts take an try, pre-experimental inquire about to be correct.The population is junior high school students in SMP Muhammadiyah 4 Pekanbaru who were taking semester of 2022/2023. There are eight classes that comprise of 21 to 31 students. The analysts chosen to utilize cluster irregular inspecting from VIII.7 lesson as the gather of students that will get the treatment. This research was conducted in 4 meetings based on the syllabus. The cruel of the pre-test score (X) accomplished by the understudies is 10.50. The change can be seen in their cruel score as appeared in post-test comes about (Y), 14.75. The edge of pre-test and post-test accomplished is 4.25. The score of sig. is 0.604 > 0.05 implies that information variation of pre-test and post-test are homogeneous. The esteem of sig. (2-tailed) is 0.013 < 0.05. Hence, it can be concluded that there's a critical contrast between the pre-test and the post-test comes about. In other word,s the elective hyphotesis of this investigate is acknowledged and the invalid hyphotesis is rejected.